Properties of Concrete Produced using Surface Modified Polyethylene Terephthalate Fibres - Michael M. Mwonga; Charles Kabubo; Naftary Gathimba (Civil Engineering Journal, 2022)
Conventional techniques of improving the bond properties of virgin Polyethylene Terephthalate Fibres reduce the mechanical strength of the fibres, are labour intensive, and present environmental hazards in the case of chemical treatment. This study introduces a new way of improving the bond properties of fibres obtained from waste Polyethylene Terephthalate bottles by coating the surface of the fibres with a thin layer of sand to counteract the above-mentioned shortcomings. Their performance was compared to that of embossed, serrated, and straight fibres and a control mix without fibres. Workability, compressive strength, tensile and flexural strength were used to assess this performance. Constant fibre length, width, and content were maintained for this exercise. Compared to the other fibres, sand-coated fibres gave the highest increment in tensile and flexural strength of 9.49% and 11.61% compared to the control mix, even though concrete’s workability and compressive strength were decreased. Furthermore, the optimization of the fibre length and content for the sand-coated fibres was carried out. The 75 mm long fibres showed the highest improvement in tensile strength of 13.76% and flexural strength of 12.49% compared to other fibre lengths. The optimum percentage of fibres was 1.25% with a 15.49% and 17.26% increment in tensile and flexural strengths, respectively. Doi: 10.28991/CEJ-2022-08-06-03 Full Text: PDF